Surgical Treatment of Epiblepharon Effectively Alleviates Keratopathy but Not Astigmatism: A Case-Control Study Utilizing Vector Analysis in East Asian Children - Shang-Te Ma; Yao-Lin Liu; Ching-Ju Hsieh; Yo-Shen Chen; Tzu-Hsun Tsai (Journal of Ophthalmology)
Purpose. To identify an appropriate surgical indication of epiblepharon by comparing keratopathy and astigmatism outcomes after surgical and medical treatments for epiblepharon in Asian children. Methods. Children diagnosed with epiblepharon (n = 82, age 5.93 ± 2.76 years) with >6 months of follow-up were enrolled. The clinical presentations and cycloplegic refractive status at the baseline and 3 and 6 months after treatment were compared between surgical (91 eyes from 47 children) and nonsurgical (67 eyes from 35 children) groups. The refractive and keratometric astigmatism at each time point were evaluated with vector analysis methods. For Thibos and Horner’s method, the astigmatic power vector was decomposed into horizontal and oblique meridians (J0 and J45). However, the treatment-induced astigmatism (TIA) vectors were calculated by Alpins’ method and depicted by the AstigMATIC software. Results. In the surgical and nonsurgical groups, the baseline astigmatism magnitude was similar (2.22 ± 1.39 and 2.26 ± 1.46 D, p = 0.87). The rate of complete resolution of keratopathy at 6 months was 71.4% and 11.5%. The astigmatism magnitude in the surgical group differed among baseline and 3 months (2.25 ± 1.23 D) and 6 months postoperatively (1.97 ± 1.28 D) (p = 0.001). Power vector analyses confirmed a nuanced against-the-rule shift in the surgical group. This trend was especially observed in the subgroup of baseline astigmatism >2.0 D. However, the difference in the astigmatism magnitude between surgical and nonsurgical groups, even in highly astigmatic children, was not significant at 6 months. Conclusions. The improvement of keratopathy in the surgical group was greater than that in the nonsurgical group in consideration of the more advanced severity in the surgery group at baseline. Decreased with-the-rule astigmatism can be observed at 6 months postoperatively, particularly among those with greater baseline astigmatism. However, the amount of change is small, and the outcome does not differ significantly from the nonsurgical treatment. Therefore, surgical indications should majorly base on the severity of symptoms and keratopathy.